2020
DOI: 10.15578/jppi.26.1.2020.47-58
|View full text |Cite
|
Sign up to set email alerts
|

LAJU TANGKAP, KARAKTERISTIK BIOLOGI DAN STATUS PEMANFAATAN UDANG JERBUNG (Penaeus merguiensis DE MANN, 1988) DAN UDANG DOGOL (Metapenaeus affinis H. MILNE EDWARDS, 1837) DI PERAIRAN CILACAP

Abstract: Sumber daya udang jerbung (Penaeus merguiensis) dan udang dogol (Metapenaeus affinis) banyak diminati masyarakat untuk dikonsumsi dan sebagai pemenuhan ekonomi masyarakat. Hal ini menyebabkan penangkapan udang yang intensif di perairan Cilacap, sehingga memerlukan pengelolaan yang lebih mendalam untuk menjaga keberlanjutannya. Penelitian ini bertujuan untuk mengkaji laju tangkap, karakteristik biologi dan status pemanfaatan udang jerbung dan udang dogol di perairan Cilacap. Penelitian lapangan dilakukan dengan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…This was confirmed in the report by Amron et al, (2009), stating the banana prawn fishing season occurs throughout the year, and peaks during the dry season (April -September). Similarly, Tirtadanu and Chodrijah (2020) showed the highest speckled shrimp and banana prawn catch from Cilacap waters using trammel nets, were obtained in March and August, respectively.…”
Section: Characteristics Of Banana Prawn (Penaeus Merguiensis) Fishery In Rembang Regencymentioning
confidence: 86%
See 1 more Smart Citation
“…This was confirmed in the report by Amron et al, (2009), stating the banana prawn fishing season occurs throughout the year, and peaks during the dry season (April -September). Similarly, Tirtadanu and Chodrijah (2020) showed the highest speckled shrimp and banana prawn catch from Cilacap waters using trammel nets, were obtained in March and August, respectively.…”
Section: Characteristics Of Banana Prawn (Penaeus Merguiensis) Fishery In Rembang Regencymentioning
confidence: 86%
“…The fishing gear used by fishermen in Indonesia comprises various types, constructions, operating methods, and parts designed to the catch target (Nurulludin et al, 2016;Wijayanto et al, 2019). In marine prawn and shrimp fisheries, a mini bottom trawl gear is usually used to catch small prawn and shrimp in shallow waters, while banana prawn (Penaeus merguiensis) is caught using trammel nets (Jamal, 2015;Nurdin and Kembaren, 2015;Tirtadanu and Ernawati, 2016;Tirtadanu et al, 2017;Tirtadanu and Panggabean, 2018;Tirtadanu and Chodrijah, 2020). Based on the Regulation of the Minister of Maritime Affairs and Fisheries Number 59 of 2020 concerning Fishing Paths and Placement of Fishing Equipment as well as Fishing Aids in WPPNRI, a trammel nets is a static and passive fishing tool (API), operated using a mesh with a size above 1.5 inches, and a P ris rope below 500 m. Fish stock density is a significant indication of fishery potential in an area, and several studies related to the stock density of prawn and shrimp resources in WPPNRI have been reported, including the report by Hargiyatno et al, (2015), where the stock of banana prawn or jerbung prawn (Penaeus merguiensis) in the Arafura Sea were estimated.…”
Section: Introductionmentioning
confidence: 99%
“…The auction is only for shrimp, specifically dogol (Panaeus mondon). According to Tirtadanu and Chodrijah (2020), the peak rate of catching dogol shrimp with trammel net in Cilacap waters was observed in March and Jerbung Shrimp in August. Moreover, the auction process running at FAP is the English type.…”
Section: Auction Processmentioning
confidence: 99%
“…Nisbah kelamin udang yang tidak seimbang karena didominasi oleh udang betina menunjukan bahwa perairan tersebut masih baik karena udang betina dapat membantu agar penambahan individu dapat berlangsung. Hasil penelitian yang sama juga ditemukan di perairan Cilacap (Tirtadanu & Chodrijah, 2020), di perairan Perbaungan (Silaen & Mulya, 2018) dan di Kupang (Marini et al, 2017).…”
Section: Nisbah Kelamin Dan Perkiraan Musim Pemijahanunclassified